Ghost squad - ROBINSON, BEN; BEN ROBINSON ([s.l.] Eastwood Publishing, 2006)
two best friends, Lucely and Syd, who accidentally unleash evil spirits in St. Augustine, Florida.
Keywords: designed to handle anti-terrorist operations with extreme precision and secrecy; the importance of family, honoring heritage, and finding courage to face challenges